2020
DOI: 10.1371/journal.pone.0240779
|View full text |Cite
|
Sign up to set email alerts
|

Capillary whole-blood IgG-IgM COVID-19 self-test as a serological screening tool for SARS-CoV-2 infection adapted to the general public

Abstract: The practicability of a prototype capillary whole-blood IgG-IgM COVID-19 self-test (Exacto ® COVID-19 self-test, Biosynex Swiss SA, Freiburg, Switzerland) as a serological screening tool for SARS-CoV-2 infection adapted to the general public was evaluated in a cross-sectional, general adult population study performed between April and May 2020 in Strasbourg, France, consisting of face-to-face, paper-based, semi-structured, and self-administrated questionnaires. Practicability was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
4
13
0
Order By: Relevance
“…The post-test answers to the satisfaction questionnaire concerning the instructions for use (sub-study 1), performing the self-test (sub-study 2), and the interpretation of the results (sub-study 3), showed that the large majority of the COVID-19 self-testing steps were considered easy or very easy by the majority of participants, as previously reported for HIV self-testing using a similar rapid test cassette [28,30]. Watching a video before the test was particularly appreciated.…”
Section: Practicability Evaluationsupporting
confidence: 53%
See 1 more Smart Citation
“…The post-test answers to the satisfaction questionnaire concerning the instructions for use (sub-study 1), performing the self-test (sub-study 2), and the interpretation of the results (sub-study 3), showed that the large majority of the COVID-19 self-testing steps were considered easy or very easy by the majority of participants, as previously reported for HIV self-testing using a similar rapid test cassette [28,30]. Watching a video before the test was particularly appreciated.…”
Section: Practicability Evaluationsupporting
confidence: 53%
“…This study aimed to evaluate the usability and clinical performance in the field of the Ag-RDST BIOSYNEX Antigen Self-Test COVID-19 Ag+ (Biosynex Swiss SA, Freiburg, Switzerland; reference 859271) for COVID-19 antigenic testing from self-collected NMT secretions in adults living in the Paris region during the third wave of the COVID-19 epidemic in France. For the first time to our knowledge, the usability of this novel Ag-RDST was evaluated according to a systematic approach based on our previous experience in assessing HIV and SARS-CoV-2 self-testing using capillary blood samples [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are two published works that evaluated the usability of SARS-CoV-2 antibodies self-testing at home 26 , 27 . In France, Tonen-Wolyec et al demonstrated high practicability of self-testing, but the performance of the self-test was supervised by an observer and the sample size was small (n = 167) 26 . In England, Atchison et al selected at random and posted rapid antibody tests to 14,400 subjects evaluating the usability through an online survey 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on HIV self-testing showed that misinterpretation occurred mainly with positive test results having a low-intensity band [39] or invalid results [26,31]. Similarly, the majority (80.0%) of misinterpreted results of COVID-19 self-test for IgG and IgM against SARS-CoV-2 concerned a weak positive IgM band [44]. This difficulty in reading some weak positive bands and in the final interpretation of HIV self-test results was previously reported in lay users as well as trained-users during professional testing [45].…”
Section: Substudymentioning
confidence: 94%
“…We previously reported that a high rate (90.2%) of adult volunteers in Kisangani and Bunia, DRC, correctly read and interpreted immunochromatographic HIV self-test using similar cassette with 2 bands of interest (HIV and control bands) [16]. Recently in France, the rate of correct interpretation of immunochromatographic self-test for IgG and IgM against SARS-CoV-2 serological screening, with 3 bands of interest (IgG and IgM to SARS-CoV-2 and control bands) was very high (98.8%) among adult volunteers [44]. The reading and interpretation of self-test for 3 diseases, as in the present, has never been yet reported in Africa.…”
Section: Substudymentioning
confidence: 99%